Resolution of Traditional Land Disputes Between PT. Nabire Baru and The Customary Community of The Waoha Tribe in Sima Village Yaur District Nabire Regency - Tanati, Daniel (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to determine the factors that cause customary land disputes between PT. Nabire Baru and the customary law community of the Waoha Tribe, Sima Village, Yaur District, Nabire Regency and to determine how to resolve customary land disputes between PT. Nabire Baru and the customary law community of the Waoha Tribe, Sima Village, Yaur District, Nabire Regency. The approach method used in this study is the normative and empirical legal approach method, namely an approach that refers to laws, literature, written regulations or other secondary legal materials, to see how it is applied through field research or the reality that occurs at the research location so that the author obtains clarity about the matter being studied. The results of this study reveal that the factors that cause customary land disputes between PT. Nabire Baru and the customary law community of the Waoha Tribe, Sima Village, Yaur District, Nabire Regency are caused by three things, namely: first, the oddity in the process of changing the designation of the Yaur District forest area; second, irregularities in the acquisition of oil palm plantation land by PT. Nabire Baru and the third result of the land dispute lawsuit and the method of resolving the customary land dispute between PT. Nabire Baru and the Waoha Tribe indigenous community, Sima Village, Yaur District, Nabire Regency has entered the National Human Rights Commission's Inquiry on the Rights of Indigenous Peoples over their territory in the Forest Area, as can be seen from the recommendation issued on December 10, 2015, signed by a member of the National Human Rights Commission, M. Imdadun Rahmat, containing 4 points to be responded to positively by the Regent of West Sumbawa, as a form of effort to protect and fulfill the Human Rights of the indigenous people of Sima Village.